Solid Model Bridge Static Damage Monitoring Based on GBSAR - Sichun LONG,Xiaoqin YUAN,Shide LU,Wenting LIU,Jinyu MA,Wenhao WU,Chuanguang ZHU (Journal of Geodesy and Geoinformation Science, 2022)
Bridge deformation monitoring usually adopts contact sensors, and the implementation process is often limited by the environment and observation conditions, resulting in unsatisfactory monitoring accuracy and effect. Ground-Based Synthetic Aperture Radar (GBSAR) combined with corner reflectors was used to perform static load-loaded deformation destruction experiments on solid model bridges in a non-contact manner. The semi parametric spline filtering and its optimization method were used to obtain the monitoring results of the GBSAR radar’s line of sight deformation, and the relative position of the corner reflector and the millimeter level deformation signals under different loading conditions were successfully extracted. The deformation transformation model from the radar line of sight direction to the vertical vibration direction was deduced. The transformation results of deformation monitoring and the measurement data such as the dial indicator were compared and analyzed. The occurrence and development process of bridge deformation and failure were successfully monitored, and the deformation characteristics of the bridge from continuous loading to eccentric loading until bridge failure were obtained. The experimental results show that GBSAR combined with corner reflector can be used for deformation feature acquisition, damage identification and health monitoring of bridges and other structures, and can provide a useful reference for design, construction and safety evaluation.